HP-NAP of Helicobacter pylori: The Power of the Immunomodulation - Codolo, Gaia; Coletta, Sara; D’Elios, Mario Milco; de Bernard, Marina (Frontiers in Immunology, 2022)
The miniferritin HP-NAP of Helicobacter pylori was originally described as a neutrophil-activating protein because of the capacity to activate neutrophils to generate oxygen radicals and adhere to endothelia. Currently, the main feature for which HP-NAP is known is the ability to promote Th1 responses and revert the immune suppressive profile of macrophages. In this review, we discuss the immune modulating properties of the protein regarding the H. pylori infection and the evidence that support the potential clinical application of HP-NAP in atopy and cancer immunotherapy.